Creating an Android-Based Early Childhood Education Application Using App Inventor Kodular - Dimas, Rifqy; M, Farhanah Fitria; Ramlan, Ramlan; Subagja, Roni Ilham (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
Creating instructional software for early childhood education in Indonesia is currently highly prominent. It is being increasingly pursued by many parties, including educational institutions, to enhance the teaching and learning experience. Most children in today's era prefer playing with smartphones over reading educational books, resulting in as many as 85% of 15 children showing reduced enthusiasm or unhappiness towards home-based learning. Parents have made significant efforts to support their children's studies. The research methodology employed in this study is a qualitative approach, explicitly utilizing descriptive analysis. Employing methodologies for gathering data. Literary Analysis Conducting a comprehensive search for references by gathering material from libraries, research articles, and internet sources, including interviews. Interrogative data analysis strategies involve directly posing questions to informants. Perception: The author researches and reviews to collect data to determine the necessary components for the application to be developed. They are developing an educational application for Android that utilizes a modular App Inventor and employs a block-based programming language. The application was designed utilizing the prototyping process. The acquired findings indicate a percentage value of 83.42%. Based on the user acceptability testing responses, this application excels in usability and benefits. The creation of this educational application has the potential to enhance the efficacy and ingenuity of the early childhood learning process by integrating interactive elements, hence fostering increased engagement and nurturing children's creativity. In order to integrate traditional methods with technology, this application incorporates numerous auditory components and integrates educational elements with entertainment, such as games and animations. This condition ensures that children remain engaged and interested during learning, fostering early childhood enthusiasm and active participation in educational activities.